Image formation device
The image forming apparatus addresses the issues of vitiligo and contamination by incorporating a two-component developer, an amorphous silicon photoconductor, and a specific intermediate transfer belt configuration, achieving effective suppression of these issues and ensuring clean image formation.
Patent Information
- Application Number
- JP2023167814
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-04-09
AI Technical Summary
Existing image forming apparatuses are ineffective in suppressing vitiligo and contamination of the charging device and photoconductor, leading to image defects and poor cleaning performance.
The image forming apparatus includes a two-component developer with a carrier and toner, a photoconductor with an amorphous silicon layer, and an intermediate transfer belt with a thermoplastic or thermosetting base resin and an electrically conductive agent. The toner particles have an external toner additive with spacer particles, and the photoreceptor surface has an arithmetic average roughness of 37 nm to 105 nm.
This configuration effectively suppresses vitiligo and contamination of the charging device and photoconductor, ensuring proper cleaning and reducing image defects.
Smart Images

Figure 2025057957000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an image forming apparatus. [Background technology]
[0002] In the electrophotographic method, for example, a two-component developer including a carrier containing carrier particles and a toner containing toner particles is used. The image forming apparatus is required to be able to suppress the occurrence of white spots (a phenomenon in which a part of an image is white) and to suppress the contamination of the charging device and the photoconductor.
[0003] The white spots are caused by, for example, carrier development (a phenomenon in which a carrier adheres to a photoconductor together with a toner when a toner image is developed on the photoconductor). In order to suppress carrier development, an image forming apparatus has been proposed that includes a carrier collecting roller that collects the carrier that adheres to the photoconductor (Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2016-071305 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, the image forming apparatus described in Patent Document 1 is not practical because it tends to be large in size, and cannot sufficiently suppress white spots. Also, the image forming apparatus described in Patent Document 1 cannot sufficiently suppress contamination of the charging device and the photoconductor.
[0006] SUMMARY OF THE PRESENT EMBODIMENT In view of the above problems, an object of the present invention is to provide an image forming apparatus capable of suppressing the occurrence of white spots and the contamination of the charging device and the photoconductor. [Means for solving the problem]
[0007] The image forming apparatus of the present invention includes a two-component developer including a carrier and a toner, a photoconductor, a charging device for charging the surface of the photoconductor, a developing device for supplying the toner to the surface of the photoconductor to develop it as a toner image, and an intermediate transfer belt to which the toner image is intermediately transferred. The intermediate transfer belt includes a base resin and a conductive agent. The base resin includes a thermoplastic resin or a thermosetting resin. The photoconductor has a substrate and an amorphous silicon photosensitive layer. The arithmetic mean roughness Ra of the surface of the photoconductor is 37 nm or more and 105 nm or less. The carrier includes carrier particles. The toner includes toner particles. The toner particles include toner base particles and a toner external additive that adheres to the surface of the toner base particles. The toner external additive includes spacer particles. The number average primary particle diameter of the spacer particles is larger than the arithmetic mean roughness Ra of the surface of the photoconductor. Effect of the Invention
[0008] The image forming apparatus of the present invention can suppress the occurrence of white spots and the contamination of the charging device and the photoconductor. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 illustrates an example of an image forming apparatus. [Diagram 2] FIG. 2 is a diagram illustrating an example of a photoconductor. [Diagram 3] 1A and 1B are diagrams illustrating an example of a state in which a toner image is transferred to a resin intermediate transfer belt included in a known image forming apparatus. [Figure 4] 1A and 1B are diagrams illustrating an example of a state in which a toner image is transferred to a rubber intermediate transfer belt included in a known image forming apparatus. [Diagram 5] FIG. 2 is a diagram illustrating an example of a developing device. [Figure 6] FIG. 2 is a diagram showing an example of carrier particles contained in a two-component developer. [Figure 7] FIG. 2 is a diagram showing an example of toner particles contained in a two-component developer. [Figure 8] FIG. 4 is a diagram showing a measuring device for measuring the image density of a toner image on an intermediate transfer belt. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] A preferred embodiment of the present invention will be described below. The carrier is an aggregate (e.g., powder) of carrier particles. The toner is an aggregate (e.g., powder) of toner particles. The external additive (toner external additive and carrier external additive) is an aggregate (e.g., powder) of external additive particles. Unless otherwise specified, the evaluation results (values indicating shape, physical properties, etc.) of powder (more specifically, powder of toner particles, powder of external additive particles, magnetic powder, powder of carrier particles, etc.) are the number average of values measured for each of a considerable number of particles selected from the powder.
[0011] Volume median diameter of powder (D 50 ) is a value measured using a laser diffraction / scattering particle size distribution analyzer (e.g., HORIBA, Ltd.'s "LA-920V2" or Beckman Coulter, Inc.'s "Coulter Counter Multisizer 3" unless otherwise specified.
[0012] Unless otherwise specified, the number average primary particle diameter of a powder is the number average value of the circle equivalent diameters of primary particles (Heywood diameter: diameter of a circle having the same area as the projected area of a primary particle) measured using a scanning electron microscope. The number average primary particle diameter of a powder is, for example, the number average value of the circle equivalent diameters of 100 primary particles. The number average primary particle diameter of particles refers to the number average primary particle diameter of particles in the powder unless otherwise specified.
[0013] Unless otherwise specified, the chargeability refers to the chargeability in triboelectric charging. For example, a standard carrier (standard carrier for negatively charged toner: N-01, standard carrier for positively charged toner: P-01) provided by the Imaging Society of Japan is mixed with the measurement target (e.g., toner) and stirred to triboelectrically charge the measurement target. The charge amount of the measurement target is measured before and after triboelectric charging, for example, with a small suction-type charge amount measuring device (Trek's "MODEL 212HS"), and the greater the change in charge amount before and after triboelectric charging, the stronger the chargeability of the measurement target.
[0014] Unless otherwise specified, the "major component" of a material means the component that is contained in the largest amount in the material on a mass basis.
[0015] The "coverage" is measured by the method described in the Examples or a method based thereon. The arithmetic mean roughness Ra of the surface of the photoreceptor was measured by a method based on JIS (Japanese Industrial Standards) B0601:2013 (Geometric Product Specifications (GPS)-Surface Quality: Profile Curve Method-Terminology, Definitions and Surface Quality Parameters).
[0016] Hereinafter, the compound and its derivatives may be collectively referred to by adding "based" after the compound name. When the polymer name is expressed by adding "based" after the compound name, it means that the repeating unit of the polymer is derived from the compound or its derivative. Acrylic and methacrylic may be collectively referred to as "(meth)acrylic". Each component described below may be used alone or in combination of two or more types, unless otherwise specified.
[0017] <Image forming device> An embodiment of the present invention relates to an image forming apparatus. The image forming apparatus of this embodiment includes a two-component developer including a carrier and a toner, a photoconductor, a charging device for charging the surface of the photoconductor, a developing device for supplying the toner to the surface of the photoconductor to develop it as a toner image, and an intermediate transfer belt to which the toner image is intermediately transferred. The intermediate transfer belt contains a base resin and a conductive agent. The base resin includes a thermoplastic resin or a thermosetting resin. The photoconductor has a substrate and an amorphous silicon photosensitive layer. The arithmetic mean roughness Ra of the surface of the photoconductor is 37 nm or more and 105 nm or less. The carrier includes carrier particles. The toner includes toner particles. The toner particles include toner base particles and a toner external additive that adheres to the surface of the toner base particles. The toner external additive includes spacer particles. The number average primary particle diameter of the spacer particles is larger than the arithmetic mean roughness Ra of the surface of the photoconductor.
[0018] In the two-component developer, for example, the carrier and the toner are stirred in the developing device, whereby the toner is charged.
[0019] An image forming apparatus 100 as an example of the image forming apparatus of the present embodiment will be described below with reference to Fig. 1. The image forming apparatus 100 shown in Fig. 1 includes a two-component developer (a developer in use D and a replenishment developer E, see Fig. 2), photoconductors 12a-12d, charging devices 21a-21d, an exposure device 22, developing devices 11a-11d, a transfer device 10, cleaning blades 23a-23d, a fixing device 17, an intermediate transfer belt cleaning device 18, and a control unit 20. Hereinafter, when there is no need to distinguish between them, each of the photoconductors 12a-12d will be referred to as a photoconductor 12, each of the charging devices 21a-21d will be referred to as a charging device 21, each of the developing devices 11a-11d will be referred to as a developing device 11, and each of the cleaning blades 23a-23d will be referred to as a cleaning blade 23.
[0020] The two-component developer includes a developer in use D and a replenishment developer E. The developer in use D includes at least an initial developer. The initial developer includes an initial carrier and a toner. The replenishment developer E includes a replenishment carrier and a toner. The initial developer and the replenishment developer E are each a two-component developer.
[0021] The photoconductor 12 is cylindrical. As shown in Fig. 2, the photoconductor 12 includes a cylindrical base 121 (e.g., a conductive base) as a support. The photoconductor 12 includes an amorphous silicon photosensitive layer 122 on the outside of the base 121. In other words, the photoconductor 12 is an amorphous silicon photoconductor. The photoconductor 12 is supported so as to be rotatable. The photoconductor 12 is driven to rotate by a motor (not shown).
[0022] The substrate 121 has a roughened surface. The roughened surface is subjected to a blasting treatment. Since the substrate 121 has a roughened surface, the surface of the amorphous silicon photosensitive layer 122 also has irregularities. In other words, the surface of the photoreceptor 12 has irregularities.
[0023] The roughened surface may be polished after the blasting process. The substrate 121 after the blasting process may have sharp edges on the surface. When the amorphous silicon photosensitive layer 122 is formed on such a substrate 121, the thickness of the amorphous silicon photosensitive layer 122 tends to become uneven. As a result, it tends to be difficult to control the arithmetic mean roughness Ra of the surface of the photoreceptor 12 to a desired range. In contrast, by performing a polishing process after the blasting process on the roughened surface, extremely protruding edges can be polished (peak cut). As the polishing material in the polishing process, a soft material (for example, nonwoven fabric, linen cloth, and paper towel) is preferable. The polishing rate during polishing is preferably 7% to 20%, more preferably 9% to 13%. The polishing rate is the difference between the arithmetic mean roughness Ra(X) of the surface of the photoreceptor 12 before the blasting treatment and the arithmetic mean roughness Ra(Y) of the surface of the photoreceptor 12 after the blasting treatment, where Ra(X) is 100%, (100×(XY) / X).
[0024] The arithmetic mean roughness Ra of the surface (circumferential surface) of the photoreceptor 12 is 37 nm or more and 105 nm or less, preferably 50 nm or more and 105 nm or less, and more preferably 50 nm or more and 80 nm or less. By setting the arithmetic mean roughness Ra of the surface of the photoreceptor 12 to 37 nm or more, the contact area between the photoreceptor 12 and the cleaning blade 23 can be reduced, and the friction coefficient can be reduced. As a result, the image forming apparatus of this embodiment can suppress wear of the cleaning blade 23 during long-term use. By setting the arithmetic mean roughness Ra of the surface of the photoreceptor 12 to 105 nm or less, the gap between the cleaning blade 23 and the photoreceptor 12 can be suppressed from becoming excessively large. As a result, the image forming apparatus of this embodiment can suppress contaminants (e.g., contamination due to transfer residual toner or toner external additives) attached to the surface of the photoreceptor 12 from slipping through the gap between the cleaning blade 23 and the photoreceptor 12. As a result, the image forming apparatus of this embodiment can properly clean the surface of the photoreceptor 12 for a long period of time and suppress the occurrence of contamination of the photoreceptor 12. Furthermore, by suppressing the occurrence of contamination of the photoreceptor 12, the image forming apparatus of this embodiment can also suppress the contamination of the charging device 21 in contact with the photoreceptor 12.
[0025] The arithmetic mean roughness Ra of the surface of the photoreceptor 12 is measured, for example, by a method conforming to JIS (Japanese Industrial Standards) B0601 (Geometrical Product Specifications (GPS)-Surface Properties: Profile Curve Method-Terminology-Definition and Surface Properties Parameters). The arithmetic mean roughness Ra of the surface of the photoreceptor 12 can be adjusted, for example, by the surface roughness of the substrate 121. The surface roughness of the substrate 121 can be adjusted by a known method. For example, the arithmetic mean roughness Ra of the surface of the photoreceptor 12 can be adjusted by changing the processing conditions when blasting the substrate 121 (more specifically, the pressure for spraying the media (abrasive grains), the distance between the nozzle of the media and the substrate surface, and the shape and material of the media, etc.). However, in the image forming apparatus of this embodiment, the substrate 121 does not need to have a roughened surface. For example, the substrate 121 may be mirror-finished. In this case, by subjecting the surface of the amorphous silicon photosensitive layer 122 to a known roughening treatment, the surface of the photoreceptor 12 can be given a desired arithmetic mean roughness Ra.
[0026] The charging device 21 charges the peripheral surface of the photoreceptor 12. In Fig. 1, the charging device 21 is a charging roller. The exposure device 22 exposes the charged peripheral surface of the photoreceptor 12 to light, thereby forming an electrostatic latent image on the peripheral surface of the photoreceptor 12. For example, the electrostatic latent image is formed on the surface layer portion (amorphous silicon photosensitive layer) of the photoreceptor 12 based on image data.
[0027] The developing device 11 develops the electrostatic latent image into a toner image with the in-use developer D. More specifically, the developing device 11 develops the electrostatic latent image formed on the circumferential surface of the photoconductor 12 with the in-use developer D, and develops the electrostatic latent image into a toner image. The photoconductor 12 then carries the toner image on its circumferential surface. The developing device 11 will be described in detail later.
[0028] The transfer device 10 includes an intermediate transfer belt 13, a driving roller 14a, a driven roller 14b, a tension roller 14c, primary transfer rollers 15a to 15d, and a secondary transfer roller 16. Hereinafter, when there is no need to distinguish between them, each of the primary transfer rollers 15a to 15d will be referred to as a primary transfer roller 15. The intermediate transfer belt 13 is an endless belt stretched around the driving roller 14a, the driven roller 14b, and the tension roller 14c. As the driving roller 14a rotates, the intermediate transfer belt 13 is transported in the clockwise direction in FIG. 1 (the direction of the arrow d1 in FIG. 1). As the intermediate transfer belt 13 is transported, the driven roller 14b and the tension roller 14c are rotated.
[0029] After the toner images are formed on the photoconductors 12a to 12d, a bias (voltage) is applied to the primary transfer rollers 15a to 15d, whereby the toner (toner images) attached to the photoconductors 12a to 12d are sequentially primarily transferred to the intermediate transfer belt 13. In this manner, toner images of multiple colors are superimposed on the intermediate transfer belt 13. After the primary transfer, a bias (voltage) is applied to the secondary transfer roller 16, whereby the toner images of multiple colors on the intermediate transfer belt 13 are secondarily transferred to the recording medium RM (e.g., printing paper) being conveyed. Then, the toner images of multiple colors superimposed on the intermediate transfer belt 13 are secondarily transferred collectively to the recording medium RM. In this manner, an image composed of unfixed toner is formed on the recording medium RM.
[0030] [Intermediate transfer belt] The intermediate transfer belt 13 contains a base resin and a conductive agent. The base resin contains a thermoplastic resin or a thermosetting resin. That is, the intermediate transfer belt 13 is made of resin. Here, a known image forming apparatus includes, for example, a rubber intermediate transfer belt or a resin intermediate transfer belt as the intermediate transfer belt. In a known image forming apparatus, a rubber intermediate transfer belt is easier to suppress the occurrence of white spots than a resin intermediate transfer belt. The reason for this will be described with reference to FIG. 3 and FIG. 4.
[0031] FIG. 3 shows an example of a state when a toner image is transferred to a resin intermediate transfer belt B1 provided in a known image forming apparatus. In FIG. 3, carrier development occurs, and a carrier C is developed on a photoconductor P together with a toner T that constitutes a toner image. The arrow indicates the direction in which the toner T is about to move. The carrier C inhibits the toner T in contact with itself from being transferred to the resin intermediate transfer belt B1. In addition, the carrier C forms a gap G1 between the resin intermediate transfer belt B1 and the photoconductor P. In the gap G1, the distance between the photoconductor P and the intermediate transfer belt B1 increases. Therefore, the toner T present in the gap G1 is difficult to transfer to the intermediate transfer belt B1. In this way, the carrier C developed on the photoconductor P by carrier development directly inhibits the transfer of the toner T in contact with itself, and at the same time, indirectly inhibits the transfer of the surrounding toner T by forming the gap G1 (hereinafter, this may be described as indirect transfer inhibition by the carrier). This causes white spots.
[0032] FIG. 4 shows an example of a state when a toner image is transferred to a rubber intermediate transfer belt B2 provided in a known image forming apparatus. In FIG. 4, carrier development occurs as in FIG. 3. However, the rubber intermediate transfer belt B2 has higher flexibility than the resin intermediate transfer belt B1 in FIG. 3. Therefore, the rubber intermediate transfer belt B2 that comes into contact with the carrier C deforms so as to envelop the carrier C. As a result, the gap G2 formed between the rubber intermediate transfer belt B2 and the photoconductor P by the carrier C becomes smaller than the gap G1 in FIG. 3. As a result, in the known image forming apparatus provided with the rubber intermediate transfer belt B2, when carrier development occurs, indirect transfer inhibition by the carrier is unlikely to occur because the gap G2 is relatively small. As a result, the known image forming apparatus provided with the rubber intermediate transfer belt B2 is likely to suppress the occurrence of white spots due to carrier development. The above has been described with reference to FIG. 3 and FIG. 4.
[0033] Thus, in known image forming devices, a rubber intermediate transfer belt is more advantageous than a resin intermediate transfer belt in terms of the occurrence of white spots. However, generally, a resin intermediate transfer belt is cleaned with a rubber blade, whereas a rubber intermediate transfer belt is cleaned with a brush. A brush has inferior cleaning performance to a rubber blade. Therefore, a rubber intermediate transfer belt has a disadvantage that it is difficult to clean residual toner adhering to the surface, compared to a resin intermediate transfer belt. Therefore, known image forming devices equipped with a rubber intermediate transfer belt are prone to image defects caused by poor cleaning of the rubber intermediate transfer belt.
[0034] In contrast, the image forming apparatus 100, which is an example of the image forming apparatus of this embodiment, is provided with a toner having a configuration described below. The toner provided in the image forming apparatus 100 has a relatively low adhesion to the photoconductor 12. Therefore, in the image forming apparatus 100, even if a gap occurs between the photoconductor 12 and the resin intermediate transfer belt 13 due to carrier development, the toner is easily transferred to the resin intermediate transfer belt 13. In other words, in the image forming apparatus 100, indirect transfer inhibition by the carrier is unlikely to occur. As a result, in the image forming apparatus 100, the merit of using the resin intermediate transfer belt 13 (the occurrence of image defects due to poor cleaning of the intermediate transfer belt can be suppressed) can be exhibited while the occurrence of white spots can be suppressed.
[0035] The content of the base resin in the intermediate transfer belt 13 is preferably 50% by mass or more and 95% by mass or less, and more preferably 70% by mass or more and 87% by mass or less. The total content of the thermoplastic resin and the thermosetting resin in the base resin in the intermediate transfer belt 13 is preferably 90% by mass or more, and more preferably 100% by mass.
[0036] Examples of the base resin include polyphenylene sulfide (PPS), polyamide (PA), polyamideimide (PAI), polyetherimide (PEI), polyimide (PI), polyetheretherketone (PEEK), polyethersulfone (PES), polyphenylsulfone (PPSU), polysulfone (PSF), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyacetal (POM), polycarbonate (PC), polyvinylidene fluoride (PVDF), polypropylene (PP), polyethylene (PE), polylactic acid (PLLA) and polyethylene naphthalate (PEN). The base resin may be a blend resin obtained by mixing the above-mentioned resins. The base resin is preferably polyamide (particularly polyamide 12), polyimide, PVDF or PET.
[0037] Examples of the conductive agent include electronic conductive agents and ionic conductive agents. Examples of the electronic conductive material include carbon black, aluminum, copper, nickel, stainless steel, tin oxide, indium oxide, titanium oxide, zinc oxide, silver, polyaniline, polyacetylene, and polyether ester amide. Examples of the ionic conductive material include inorganic ionic conductive materials and organic ionic conductive materials. Examples of the inorganic ionic conductive material include sodium perchlorate, lithium perchlorate, calcium perchlorate, and lithium chloride. Examples of the organic ionic conductive material include modified aliphatic dimethylethyl ammonium ethosulfate, stearyl ammonium acetate, lauryl ammonium acetate, octadecyl trimethyl ammonium perchlorate, sulfate, ethosulfate salt, methyl sulfate salt, phosphate, hydrofluoric acid salt, and acetate. Examples of the conductive agent include carbon black, titanium oxide, and polyether ester amide.
[0038] In the intermediate transfer belt 13, the content of the conductive agent is preferably 10 parts by weight or more and 80 parts by weight or less, and more preferably 17 parts by weight or more and 30 parts by weight or less, relative to 100 parts by weight of the base resin.
[0039] The intermediate transfer belt 13 can be produced, for example, by mixing the above-mentioned base resin (or its precursor), the conductive material, and other components (for example, a solvent) that are added as necessary, and then molding the mixture into a belt shape. Specific molding methods include, for example, an extrusion molding method, an inflation method, a blow molding method, a dipping method, and a centrifugal molding method.
[0040] After the secondary transfer, the fixing device 17 heats and pressurizes the toner on the recording medium RM to fix the toner to the recording medium RM. In this manner, an image made of the fixed toner is formed on the recording medium RM.
[0041] The intermediate transfer belt cleaning device 18 cleans the toner remaining on the intermediate transfer belt 13 after the secondary transfer.
[0042] The control unit 20 electronically controls the operation of the image forming apparatus 100 based on the outputs of various sensors. The control unit 20 includes, for example, a central processing unit (CPU), a random access memory (RAM), and a storage device that stores programs and rewritably stores predetermined data. A user gives instructions (for example, electrical signals) to the control unit 20 through an input unit (not shown). The input unit is, for example, a keyboard, a mouse, or a touch panel.
[0043] [Developing device] Next, the developing device 11 provided in the image forming apparatus 100 will be described in more detail with reference to Fig. 5. Fig. 5 shows the developing device 11 and its surroundings of the image forming apparatus 100 shown in Fig. 1. The developing device 11 has at least a developer carrier 111, a storage section 114, and a supply section 115. The developing device 11 further has a regulating blade 112, a plurality of stirring shafts 113, and a discharge section 116.
[0044] The storage section 114 stores the developer D in use (i.e., the stored developer) and a plurality of stirring shafts 113. The developer D in use stored in the storage section 114 includes at least an initial developer. The plurality of stirring shafts 113 include a first stirring shaft 113a and a second stirring shaft 113b. The first stirring shaft 113a has a spiral stirring blade. The second stirring shaft 113b has a spiral stirring blade that faces in the opposite direction (opposite phase) to the spiral blade of the first stirring shaft 113a. The first stirring shaft 113a stirs the developer D in use in the storage section 114, and transports the developer D in use in a first transport direction (a direction perpendicular to the paper surface of FIG. 5 and a direction from the back to the front of the paper surface) from one end side to the other end side in the axial direction of the developer carrier 111. The second agitating shaft 113b transports the in-use developer D in a second transport direction opposite to the first transport direction while agitating the in-use developer D in the storage section 114. As the in-use developer D, which contains toner and carrier, is agitated, the toner is charged by friction with the carrier, and the charged toner is carried by the carrier. The second agitating shaft 113b supplies the in-use developer D to the developer carrier 111 while transporting the in-use developer D in the second transport direction.
[0045] The supply unit 115 is provided on the upper part of the storage unit 114. The supply unit 115 supplies the supply developer E to the storage unit 114. The supply unit 115 has a supply amount adjustment member 115a and a developer container 115b.
[0046] The supply amount adjustment member 115a controls the supply amount of the replenishment developer E supplied from the developer container 115b to the storage portion 114. The supply amount adjustment member 115a is composed of, for example, a screw shaft whose rotation operation is controlled by the control portion 20. For example, the supply amount of the replenishment developer E can be changed according to the amount of rotation of the screw shaft.
[0047] The developer container 115b accommodates the replenishment developer E. The replenishment developer E in the developer container 115b is supplied to the accommodation portion 114.
[0048] The discharge section 116 discharges the developer D in use from the storage section 114. The discharge section 116 includes a discharge path 116a and a collection container 116b. The discharge path 116a connects the storage section 114 and the collection container 116b. When the amount of the developer D in use in the storage section 114 exceeds a predetermined amount, the excess developer D in use enters the discharge path 116a from the opening on the upper end side of the discharge path 116a. The predetermined amount is, for example, an amount determined by the upper end position of the discharge path 116a. The excess developer D in use is, for example, the amount of developer D in use that exceeds the predetermined amount. When the excess developer D in use enters the discharge path 116a, it advances downward inside the discharge path 116a by gravity and flows into the collection container 116b. Then, the collection container 116b stores the excess developer D in use. Hereinafter, the collected developer is referred to as a collected developer F.
[0049] In an unused image forming apparatus 100 (for example, after being shipped from the factory and before printing is started), the developer D currently being used and stored in the storage section 114 is an initial developer.
[0050] After the image forming apparatus 100 starts to be used (for example, after printing starts), before the replenishing unit 115 replenishes the replenishment developer E into the storage unit 114, the in-use developer D stored in the storage unit 114 is the initial developer. In the storage unit 114, the initial developer is stirred by the stirring shaft 113, and the toner contained in the initial developer is triboelectrically charged. Then, the stirred initial developer is carried on the developer carrier 111.
[0051] When the image forming apparatus 100 continues printing, the replenishment developer E is replenished into the storage section 114, and the used developer D is discharged from the storage section 114. Therefore, when the image forming apparatus 100 continues printing, the used developer D stored in the storage section 114 is gradually replaced with the replenishment developer E replenished from the replenishing section 115. Therefore, after the replenishing section 115 replenishes the replenishment developer E into the storage section 114, the used developer D stored in the storage section 114 is the initial developer and the replenishment developer E. After the replenishing section 115 replenishes the replenishment developer E into the storage section 114, the initial developer and the replenishment developer E are stirred by the stirring shaft 113 in the storage section 114, and the toner contained in the initial developer and the toner contained in the replenishment developer E are triboelectrically charged. Then, the stirred initial developer and the replenishment developer E are carried on the developer carrying member 111.
[0052] The developing device 11 is a so-called trickle development type developing device 11 having a storage section 114, a replenishing section 115, and a discharging section 116. The trickle development type developing device 11 starts developing an electrostatic latent image with an initial developer in the storage section 114, and then develops the electrostatic latent image with the developer D in use in the storage section 114 while discharging the developer D in use in the storage section 114 and replenishing the replenishing developer E into the storage section 114. During image formation, the carrier is replenished into the storage section 114 together with the toner, and the carrier in the storage section 114 is discharged only in an amount that is excessive due to the replenishing, thereby suppressing deterioration of the carrier in the storage section 114. Furthermore, suppressing deterioration of the carrier can reduce the number of times the carrier in the developing device 11 is replaced.
[0053] The developer carrier 111 is disposed opposite the photoconductor 12 via a development gap g. The development gap g is a gap between the developer carrier 111 and the photoconductor 12 at the closest portion. The developer carrier 111 includes a magnet roll and a development sleeve. The magnet roll has magnetic poles at least on its surface layer portion. The magnetic poles are, for example, N poles and S poles based on permanent magnets. The development sleeve is a non-magnetic cylinder (for example, an aluminum pipe). The magnet roll is located inside the development sleeve (inside the cylinder), and the development sleeve is located on the surface portion of the developer carrier 111. The shaft of the magnet roll and the development sleeve are connected via a flange so that the development sleeve can rotate around the non-rotating magnet roll.
[0054] As already described, the charged toner is carried by the carrier in the storage section 114. The developer carrier 111 (specifically, the developing sleeve) attracts the carrier in the storage section 114 by magnetic force while rotating in the clockwise direction in FIG. 5 (the direction of the arrow d2 in FIG. 5), and carries a chain made of carrier particles carrying toner particles (i.e., a magnetic brush of the developer D in use) on its circumferential surface. In this way, the developer carrier 111 carries the developer D in use in the storage section 114 on its circumferential surface, and transports the developer D in use in the direction of the arrow d2.
[0055] The regulating blade 112 regulates the magnetic brush of the developer D in use formed on the circumferential surface of the developer carrier 111 to a predetermined thickness.
[0056] After the thickness of the magnetic brush is regulated by the regulating blade 112, the developer carrier 111 (specifically, the developing sleeve) further rotates in the clockwise direction (the direction of the arrow d2 in FIG. 5), and the developer D in use is transported to the development gap g. The photoconductor 12 rotates in the counterclockwise direction in FIG. 5 (the direction of the arrow d3 in FIG. 5). A bias (voltage) is applied to the developer carrier 111, and a potential difference occurs between the surface potential of the developer carrier 111 and the surface potential of the photoconductor 12. Due to this potential difference, the toner contained in the developer D in use carried by the developer carrier 111 moves to the circumferential surface of the photoconductor 12. In detail, the charged toner contained in the developer D in use carried by the developer carrier 111 is attracted by an electric force to an electrostatic latent image (for example, an exposed portion whose potential is lower than that of a non-exposed portion due to exposure) formed on the photoconductor 12, and moves to the electrostatic latent image on the photoconductor 12. As a result, a toner image is formed on the peripheral surface of the photoreceptor 12 .
[0057] A detailed description will be given later of the developer provided in the image forming apparatus 100. As already described, the developer includes the in-use developer D and the replenishment developer E. The in-use developer D includes at least the initial developer.
[0058] Carrier development is a defect in which carrier particles in a magnetic brush (i.e., a chain of carrier particles carrying toner particles) carried by the developer carrier 111 migrate to the photoreceptor 12. Once the carrier particles have migrated to the photoreceptor 12, they have a strong adhesive force, making it difficult for the carrier particles to return to the developer carrier 111. The carrier particles that have migrated to the photoreceptor 12 are one cause of white spots.
[0059] The width DS of the development gap g is preferably 0.100 mm or more and 1.000 mm or less, and more preferably 0.200 mm or more and 0.500 mm or less.
[0060] The image forming apparatus 100 has been described above with reference to FIGS. 1 to 5. However, the image forming apparatus of this embodiment is not limited to the image forming apparatus 100 shown in FIG. 1. For example, the image forming apparatus of this embodiment may be an image forming apparatus for forming a monochrome image. The image forming apparatus of this embodiment may employ a rotary system. The charging device may be a charging device other than a charging roller (for example, a scorotron charger, a charging brush, or a corotron charger). In the image forming apparatus of this embodiment, configurations other than the two-component developer, the photoconductor, the charging device, the developing device, and the intermediate transfer belt may be omitted. The image forming apparatus of this embodiment may not employ a trickle development system.
[0061] [Two-component developer] The two-component developer provided in the image forming apparatus of this embodiment will be described in detail below. The two-component developer includes a toner and a carrier. The toner includes toner particles. The carrier includes carrier particles. The two-component developer is, for example, a two-component developer (hereinafter sometimes referred to as a general developer) used in an image forming apparatus that does not use a trickle development method, an initial developer used in an image forming apparatus that uses a trickle development method, or a replenishment developer used in an image forming apparatus that uses a trickle development method.
[0062] The two-component developer can be obtained by mixing the carrier and the toner while stirring them using, for example, a mixer (more specifically, for example, a bowl mill and a rocking mixer (registered trademark)).
[0063] In general developers, the toner ratio (100×toner mass / carrier mass), which indicates the ratio of the toner mass to the carrier mass, is preferably 1% to 20%, and more preferably 5% to 15%. In refill developers, the carrier ratio (100×carrier mass / toner mass), which indicates the ratio of the carrier mass to the toner mass, is preferably 2% to 30%, and more preferably 5% to 20%.
[0064] [Carrier particles] An example of a carrier particle contained in a carrier will be described below with reference to the drawings. FIG. 6 shows a carrier particle 1, which is an example of a carrier particle. The carrier particle 1 has a carrier base particle 2 and a carrier external additive 3. The carrier base particle 2 includes a carrier core 2a and a coating layer 2b that coats the surface of the carrier core 2a. The coating layer 2b contains a coating resin. The coating layer 2b coats the entire surface of the carrier core 2a.
[0065] The carrier particles 1 have been described above with reference to FIG. 6. However, the carrier particles contained in the carrier are not limited to the carrier particles 1 shown in FIG. 6. For example, the coating layer may cover at least a part of the carrier core. That is, a part of the carrier core may be exposed. The coating layer may have a multi-layer structure. Furthermore, the carrier particles may not have an external carrier additive. Furthermore, the carrier base particles may not have a coating layer.
[0066] (Career Core) The carrier core preferably contains a magnetic material. The carrier core may be a particle of a magnetic material, or may be a particle including a carrier core binder resin and particles of a magnetic material dispersed in the carrier core binder resin (hereinafter, may be referred to as a resin carrier core).
[0067] Examples of the magnetic material contained in the carrier core include ferromagnetic metals (more specifically, for example, iron, cobalt, nickel, and alloys containing one or more of these metals) and ferromagnetic metal oxides. Examples of the ferromagnetic metal oxide include ferrite and magnetite, which is a type of spinel ferrite. Examples of the ferrite include Ba ferrite, Mn ferrite, Mn-Zn ferrite, Ni-Zn ferrite, Mn-Mg ferrite, Ca-Mg ferrite, Li ferrite, Cu-Zn ferrite, and Mn-Mg-Sr ferrite. Examples of the method for producing the carrier core include a method including a step of crushing and firing a magnetic material. In the production of the carrier core, the saturation magnetization of the carrier can be adjusted by changing the amount of magnetic material added (particularly the ratio of the ferromagnetic material). In the production of the carrier core, the circularity of the carrier core can be adjusted by changing the firing temperature. In addition, the carrier core may be a commercially available product.
[0068] Examples of magnetic material particles used as carrier cores include ferrite particles. Ferrite particles tend to have sufficient magnetism for image formation using a two-component developer. Ferrite particles manufactured by a general manufacturing method tend not to be perfectly spherical and tend to have moderate irregularities on the surface. When the carrier core is a ferrite particle (ferrite core), from the viewpoint of improving the adhesion between the surface of the ferrite core and the coating layer, the arithmetic mean roughness of the surface of the ferrite core (more specifically, the arithmetic mean roughness Ra defined in JIS (Japanese Industrial Standards) B0601:2013) is preferably 0.3 μm or more and 2.0 μm or less.
[0069] The binder resin in the resin carrier core is preferably a polyester resin, a urethane resin, or a phenol resin, and more preferably a phenol resin. The magnetic material particles in the resin carrier core include, for example, particles containing one or more of the magnetic materials exemplified in the magnetic material.
[0070] In the carrier particles, the mass ratio of the carrier core to the total mass of the carrier core and the coating layer is preferably from 80% by mass to 99% by mass, and more preferably from 95% by mass to 99% by mass.
[0071] The number-average primary particle diameter of the carrier core is preferably 20 μm or more and 60 μm or less. By making the number-average primary particle diameter of the carrier core 20 μm or more, the occurrence of carrier developing can be suppressed. By making the number-average primary particle diameter of the carrier core 60 μm or less, the developability can be optimized.
[0072] The saturation magnetization of the carrier core in an applied magnetic field of 3000 Oe is preferably 60 emu / g or more and 80 emu / g or less. By setting the saturation magnetization of the carrier core to 60 emu / g or more, the occurrence of carrier development can be suppressed. By setting the saturation magnetization of the carrier core to 80 emu / g or less, the developability can be optimized.
[0073] (Coat layer) The coating layer contains a coating resin. The coating layer preferably further contains at least one of metal oxide particles and carbon black. The thickness of the coating layer is, for example, 0.3 μm or more and 2.0 μm or less.
[0074] The mass of the coating layer relative to 100 parts by mass of the carrier core is preferably 0.5 parts by mass or more and 10.0 parts by mass or less, more preferably 1.0 parts by mass or more and 3.0 parts by mass or less. By making the mass of the coating layer 0.5 parts by mass or more, the exposure of the carrier core can be suppressed. By making the mass of the coating layer 5.0 parts by mass or less, the carrier can easily charge the toner.
[0075] Examples of the coating resin include fluororesins and silicone resins. Silicone resins are preferred as the coating resin. The content of the coating resin in the coating layer is preferably 50.0% by mass or more and 90.0% by mass or less, and more preferably 70.0% by mass or more and 85.0% by mass or less. The content of the silicone resin in the coating resin is preferably 90% by mass or more, and more preferably 100% by mass.
[0076] (Silicone resin) Silicone resin is a resin having a polysiloxane structure (e.g., an alkyl polysiloxane structure). Examples of silicone resins include silicone resins having a methyl group and epoxy resin-modified silicone resins. Examples of silicone resins having a methyl group include silicone resins having a methyl group and no phenyl group (hereinafter sometimes referred to as "methyl silicone resins"), and silicone resins having a methyl group and a phenyl group (hereinafter sometimes referred to as "methyl phenyl silicone resins"). As the silicone resin, methyl silicone resins are preferred.
[0077] (metal oxide particles) As the metal oxide particles, ferroelectric metal oxide particles (e.g., strontium titanate particles or barium titanate particles) are preferred, and barium titanate particles are more preferred. When the coating layer contains metal oxide particles, the two-component developer can easily impart a desired charge amount to the toner. Furthermore, when the coating layer contains metal oxide particles (particularly, barium titanate particles), the strength of the coating layer can be optimized, and the carrier external additive can be prevented from being embedded in the coating layer.
[0078] The number-average primary particle diameter of the metal oxide particles is preferably 100 nm or more and 500 nm or less, and more preferably 250 nm or more and 350 nm or less. By making the number-average primary particle diameter of the metal oxide particles 100 nm or more, the two-component developer can more easily impart a desired charge amount to the toner. By making the number-average primary particle diameter of the metal oxide particles 500 nm or less, it is possible to suppress the metal oxide particles from being detached from the coating layer.
[0079] In the coating layer, the content of the metal oxide particles relative to 100 parts by mass of the coating resin is preferably 5 parts by mass or more and 50 parts by mass or less, and more preferably 10 parts by mass or more and 30 parts by mass or less. By making the content of the metal oxide particles 5 parts by mass or more, the two-component developer can more easily impart a desired charge amount to the toner. By making the content of the metal oxide particles 50 parts by mass or less, it is possible to suppress the metal oxide particles from being detached from the coating layer.
[0080] (Carbon Black) Carbon black promotes charge migration in the coating layer, making it easier for the two-component developer to impart a desired amount of charge to the toner.
[0081] The number-average primary particle diameter of the carbon black is preferably 10 nm or more and 200 nm or less, more preferably 20 nm or more and 60 nm or less. By making the number-average primary particle diameter of the carbon black particles 10 nm or more, the two-component developer can more easily impart a desired charge amount to the toner. By making the number-average primary particle diameter of the carbon black particles 200 nm or less, it is possible to suppress the carbon black from being detached from the coating layer.
[0082] In the coating layer, the content of carbon black relative to 100 parts by mass of the coating resin is preferably 1 part by mass or more and 20 parts by mass or less, more preferably 6 parts by mass or more and 12 parts by mass or less. By making the content of carbon black 1 part by mass or more, the two-component developer can more easily impart a desired charge amount to the toner. By making the content of carbon black 20 parts by mass or less, it is possible to suppress the carbon black from being detached from the coating layer.
[0083] (Other ingredients) The coating layer may further contain other components in addition to the coating resin, the metal oxide particles, and the carbon black, such as a charge control agent, an adhesion improver, and a crosslinking agent.
[0084] (External carrier additive) The carrier external additive optimizes the fluidity of the carrier and promotes the transfer of charge from the carrier particles to the toner particles. Examples of the carrier external additive include metal oxide particles. Examples of the metal oxide particles include the same particles as those exemplified as the metal oxide particles contained in the above-mentioned coating layer. The carrier external additive preferably contains strontium titanate particles. The content of strontium titanate in the carrier external additive is preferably 90% by mass or more, more preferably 100% by mass.
[0085] The strontium titanate particles may be doped. When the strontium titanate particles are doped, the amount of the doped element may be 1.00% by mass or less, 0.10% by mass or less, or less than 0.01% by mass, based on the total mass of the strontium titanate particles. However, the strontium titanate particles may not be doped. The strontium titanate particles may be composed of undoped strontium titanate. For example, the strontium titanate particles may be composed of strontium titanate that is not doped with lanthanum and a Group 5 element of the periodic table (e.g., niobium, tantalum).
[0086] The number average primary particle diameter of the external carrier additive is preferably 15 nm or more and 85 nm or less, more preferably 20 nm or more and 70 nm or less, and even more preferably 25 nm or more and 40 nm or less.
[0087] The number-average primary particle diameter of the carrier external additive is preferably smaller than the arithmetic mean roughness Ra of the surface of the photoconductor for the following reasons. As described above, the surface of the photoconductor has unevenness. For this reason, the toner components (e.g., binder resin and release agent) may adhere to the recesses on the surface of the photoconductor. If the toner components are maintained in the recesses on the surface of the photoconductor, the charging performance of the photoconductor may be reduced. In contrast, by adopting the above-mentioned configuration, when the magnetic brush and the photoconductor come into contact with each other during development, the carrier external additive contained in the magnetic brush can penetrate into the recesses on the surface of the photoconductor and scrape out the toner components from the recesses. As a result, the image forming apparatus of this embodiment can more effectively suppress contamination of the photoconductor.
[0088] From the viewpoint of forming an image having a desired image density and little fog, the amount of the carrier external additive is preferably 0.01 parts by mass to 0.20 parts by mass, more preferably 0.02 parts by mass to 0.06 parts by mass, per 100.00 parts by mass of the carrier base particles.
[0089] The coverage of the carrier external additive on the carrier particles is preferably 5.0 area% or more and 35.0 area% or less, and more preferably 10.0 area% or more and 20.0 area% or less. By setting the coverage of the carrier external additive to 5.0 area% or more, the carrier external additive can easily exert its function. By setting the coverage of the carrier external additive to 35.0 area% or less, the carrier external additive can be prevented from being detached from the carrier base particles.
[0090] (Carrier Manufacturing Method) The method for producing the carrier includes, for example, a step of forming carrier base particles and a step of adding an external additive to the carrier base particles.
[0091] (Carrier mother particle formation process) In this step, a coating liquid is applied to the surface of the carrier core. The coating liquid contains a coating resin and a solvent. The solid content of the coating liquid is preferably 10% by mass or more and 30% by mass or less.
[0092] Examples of the solvent for the coating liquid include lactam compounds (e.g., 2-pyrrolidone and N-methyl-2-pyrrolidone), ketone compounds (e.g., methyl ethyl ketone and methyl isobutyl ketone), cyclic ether compounds (e.g., tetrahydrofuran and tetrahydropyran), alcohol compounds (e.g., normal butanol and isobutanol), ester solvents (e.g., ethyl acetate and isobutyl acetate), and aromatic hydrocarbon compounds (e.g., toluene and xylene).Toluene is preferred as the solvent for the coating liquid.
[0093] Examples of methods for applying the coating liquid to the surface of the carrier core include a method of immersing the carrier core in the coating liquid and a method of spraying the coating liquid onto the carrier core in the fluidized bed. In the method of immersing the carrier core in the coating liquid, a small amount of the coating liquid is applied to the convex parts of the surface of the carrier core, while a large amount of the coating liquid is applied to the concave parts of the surface of the carrier core, so the amount of the coating liquid tends to be uneven. In contrast, in the method of spraying the coating liquid onto the carrier core in the fluidized bed, the coating liquid tends to be applied uniformly to both the convex parts and the concave parts of the surface of the carrier core. From the above, the method of spraying the coating liquid onto the carrier core in the fluidized bed is preferred as the method for applying the coating liquid onto the surface of the carrier core.
[0094] In this process, the carrier cores after the coating process are heated to remove the solvent contained in the coating liquid. If the coating liquid contains an uncured coating resin, the uncured coating resin is thermally cured. As a result, a coating layer is formed from the coating liquid. The heating temperature during heating is preferably 100°C or higher and 300°C or lower, more preferably 180°C or higher and 220°C or lower. The heating time during heating is preferably 30 minutes or higher and 90 minutes or lower, more preferably 50 minutes or higher and 70 minutes or lower.
[0095] (External addition process to carrier base particles) In this step, for example, a mixer is used to mix the carrier base particles with the carrier external additive. By mixing, the carrier external additive adheres to the surface of the carrier base particles, and a carrier containing the carrier particles is obtained. The mixing in the external addition step to the carrier base particles is preferably performed under conditions in which the carrier external additive is not completely embedded in the carrier base particles.
[0096] [toner] The toner includes toner particles. The toner particles include toner base particles and toner external additives attached to the surfaces of the toner base particles. The toner external additives include spacer particles. Hereinafter, the toner will be described in detail with reference to the drawings as appropriate.
[0097] Fig. 7 shows an example of a toner particle 4 contained in the toner. The toner particle 4 shown in Fig. 7 includes a toner base particle 5 and an external toner additive 6 attached to the surface of the toner base particle 5. The external toner additive 6 includes spacer particles 6a and silica particles 6b.
[0098] The toner particles have been described above with reference to the drawings. However, the toner particles may have a structure different from that of the toner particle 4 shown in FIG. 7. Specifically, the toner external additive may contain only spacer particles. In addition, the toner external additive may contain other toner external additive particles other than the spacer particles and silica particles. The toner mother particles may be capsule toner particles that contain a toner core and a shell layer that covers the toner core.
[0099] (Toner additive) The toner external additive adheres to the surface of the toner base particle. The toner external additive includes spacer particles. The toner external additive preferably further includes base silica particles that do not fall under the category of spacer particles. The toner external additive may further include particles other than the spacer particles and base silica particles (hereinafter, other toner external additive particles). The total content of the spacer particles and base silica particles in the toner external additive is preferably 60% by mass or more and 90% by mass or less.
[0100] (Spacer particles) The number average primary particle diameter of the spacer particles is larger than the arithmetic mean roughness Ra of the surface of the photoreceptor. The number average primary particle diameter of the spacer particles is preferably 38 nm or more and 140 nm or less, more preferably 45 nm or more and 140 nm or less, even more preferably 65 nm or more and 120 nm or less, and particularly preferably 90 nm or more and 110 nm or less. By making the number average primary particle diameter of the spacer particles 38 nm or more, the function of the spacer particles can be effectively exhibited. By making the number average primary particle diameter of the spacer particles 140 nm or less, the detachment of the spacer particles from the toner mother particles can be effectively suppressed.
[0101] Examples of the spacer particles include silica particles (hereinafter, the silica particles used as the spacer particles may be referred to as "spacer silica particles"), resin particles, aluminum oxide particles, magnesium oxide particles, zinc oxide particles, and composite particles combining these. As the spacer particles, spacer silica particles or resin particles are preferred, and resin particles are more preferred. By using resin particles as the spacer particles, the melting property of the toner can be optimized.
[0102] The resin contained in the spacer particles is preferably a styrene-(meth)acrylic resin. The content of the styrene-(meth)acrylic resin in the spacer particles is preferably 70% by mass or more, more preferably 95% by mass or more, and even more preferably 100% by mass.
[0103] Styrene-(meth)acrylic resin is a copolymer of a styrene compound and a (meth)acrylic acid compound. Examples of the (meth)acrylic acid compound include (meth)acrylic acid, (meth)acrylonitrile, and (meth)acrylic acid alkyl esters (particularly, (meth)acrylic acid alkyl esters having an alkyl group having 1 to 4 carbon atoms in the ester moiety). As the (meth)acrylic acid compound, (meth)acrylic acid alkyl esters are preferred.
[0104] Examples of the styrene compound include styrene, alkylstyrenes (more specifically, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, ethylstyrene, 2,3-dimethylstyrene, 2,4-dimethylstyrene, o-tert-butylstyrene, m-tert-butylstyrene, and p-tert-butylstyrene), and halogenated styrenes (more specifically, α-chlorostyrene, o-chlorostyrene, m-chlorostyrene, and p-chlorostyrene). As the styrene compound, styrene is preferred.
[0105] The content of the first repeating unit derived from a styrene compound relative to all repeating units contained in the styrene-(meth)acrylic resin is preferably from 5.0% by mass to 40.0% by mass, more preferably from 15.0% by mass to 25.0% by mass.
[0106] Examples of the (meth)acrylic acid alkyl ester include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, iso-propyl (meth)acrylate, butyl (meth)acrylate (specifically, n-butyl (meth)acrylate), iso-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. As the (meth)acrylic acid alkyl ester, butyl (meth)acrylate is preferred.
[0107] The content ratio of the second repeating unit derived from the (meth)acrylic acid compound relative to all repeating units contained in the styrene-(meth)acrylic resin is preferably 20.0 mass % or more and 60.0 mass % or less, and more preferably 35.0 mass % or more and 45.0 mass % or less.
[0108] The styrene-(meth)acrylic resin preferably further has a third repeating unit derived from a crosslinking agent. That is, the styrene-(meth)acrylic resin is preferably a crosslinked styrene-(meth)acrylic resin having a first repeating unit derived from a styrene compound, a second repeating unit derived from a (meth)acrylic acid compound, and a third repeating unit derived from a crosslinking agent. When the spacer particle contains such a crosslinked styrene-(meth)acrylic resin, the spacer particle is given an appropriate rigidity, and it becomes easy to function as a spacer particle.
[0109] Examples of the crosslinking agent include compounds having two or more vinyl groups.Specific examples of the crosslinking agent include N,N'-methylenebisacrylamide, divinylbenzene, ethylene glycol diacrylate, ethylene glycol dimethacrylate, diethylene glycol diacrylate, tetraethylene glycol diacrylate, polyethylene glycol diacrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, tripropylene glycol diacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, 1,4-butanediol dimethacrylate, and 1,6-hexanediol dimethacrylate.As the crosslinking agent, divinylbenzene is preferable.
[0110] The content ratio of the third repeating unit relative to the total repeating units of the styrene-(meth)acrylic resin is preferably 20.0% by mass or more and 60.0% by mass or less, more preferably 35.0% by mass or more and 45.0% by mass or less. By making the content ratio of the third repeating unit 20.0% by mass or more, the spacer particles are given appropriate rigidity, and the spacer particles can more easily perform their function as spacers. By making the content ratio of the third repeating unit 60.0% by mass or less, the hardness of the spacer particles becomes excessively high, and the surface of the photoreceptor can be effectively prevented from being polished.
[0111] The crosslinked resin preferably has a repeating unit derived from styrene, a repeating unit derived from butyl methacrylate, and a repeating unit derived from divinylbenzene.
[0112] From the viewpoint of fully exerting the function of the spacer particles while suppressing detachment from the toner mother particles, the content of the spacer particles in the toner particles is preferably 0.10 parts by mass or more and 5.00 parts by mass or less, more preferably 0.40 parts by mass or more and 2.20 parts by mass or less, and even more preferably 0.80 parts by mass or more and 1.50 parts by mass or less, relative to 100.00 parts by mass of the toner mother particles. By making the content of the spacer particles 0.10 parts by mass or more, it becomes easy to fully exert the function as the spacer particles. By making the content of the spacer particles 5.00 parts by mass or less, it is possible to suppress the spacer particles from being detached from the toner mother particles.
[0113] The coverage of the spacer particles on the toner particles is preferably 7% by area or more and 45% by area or less, more preferably 15% by area or more and 35% by area or less. By making the coverage of the spacer particles 7% by area or more, the spacer particles can easily exert their functions. By making the coverage of the spacer particles 45% by area or less, the spacer particles can be prevented from being detached from the toner base particles.
[0114] When the spacer particles are resin particles, the resin particles can be produced by known methods (e.g., suspension polymerization and phase inversion emulsification). Polymerization initiators used in the production of resin particles include, for example, inorganic peroxides (e.g., potassium persulfate, ammonium persulfate, and hydrogen peroxide), organic peroxides (e.g., t-butyl peroxide, cumene hydroxyperoxide, and paramenthane peroxide), and azo compounds (e.g., azobisdiisobutylnitrile and 2,2'-azobis(2-amidinopropane)dihydrochloride), and inorganic peroxides or organic peroxides are preferred.
[0115] When the spacer particles are spacer silica particles, the spacer silica particles can be produced, for example, by a dry method. The spacer silica particles may be subjected to at least one of a positive charging treatment and a hydrophobic treatment by a surface treatment agent.
[0116] (Base silica particles) The number average primary particle diameter of the base silica particles is smaller than the arithmetic mean roughness Ra of the surface of the photoreceptor. As the base silica particles, silica particles that have been subjected to a surface treatment to impart hydrophobicity are preferred. The number average primary particle diameter of the base silica particles is preferably 20 nm or more and 60 nm or less, more preferably 20 nm or more and 35 nm or less. By setting the number average primary particle diameter of the base silica particles to 20 nm or more, it is possible to prevent the base silica particles from being embedded in the toner mother particles. In addition, by setting the number average primary particle diameter of the base silica particles to 60 nm or less, it is possible to prevent the base silica particles from being detached from the toner mother particles.
[0117] In order to fully exert the function of the base silica particles while suppressing detachment from the toner base particles, the content of the base silica particles in the toner particles is preferably 0.10 parts by mass or more and 10.00 parts by mass or less, and more preferably 0.50 parts by mass or more and 2.50 parts by mass or less, per 100.00 parts by mass of the toner base particles.
[0118] (Other toner additive particles) The number average primary particle diameter of the other toner external additive particles is smaller than the arithmetic mean roughness Ra of the surface of the photoreceptor. As the other toner external additive particles, metal oxide particles (more specifically, aluminum oxide particles, titanium oxide particles, magnesium oxide particles, zinc oxide particles, strontium titanate particles, or barium titanate particles) are preferred, and aluminum oxide particles are more preferred. The number average primary particle diameter of the aluminum oxide particles is preferably 5 nm or more and 50 nm or less, and more preferably 10 nm or more and 20 nm or less. The number average primary particle diameter of the strontium titanate particles is preferably 10 nm or more and 50 nm or less, and more preferably 20 nm or more and 40 nm or less.
[0119] The content of the other toner external additives is preferably from 0.10 parts by mass to 5.00 parts by mass, and more preferably from 1.00 parts by mass to 2.00 parts by mass, relative to 100.00 parts by mass of the toner base particles, from the viewpoint of fully exerting their functions while suppressing detachment from the toner base particles.
[0120] (Toner base particles) The toner base particles contain, for example, a binder resin and at least one selected from the group consisting of a colorant, a charge control agent, and a release agent. The binder resin, the colorant, the charge control agent, and the release agent will be described below.
[0121] (Binding resin) In order to obtain a toner having excellent low-temperature fixing properties, the toner base particles preferably contain a thermoplastic resin as a binder resin, and more preferably contain a thermoplastic resin at a ratio of 85% by mass or more of the total binder resin. Examples of the thermoplastic resin include polyester resin, styrene resin, acrylic acid ester resin (more specifically, acrylic acid ester polymer, methacrylic acid ester polymer, etc.), olefin resin (more specifically, polyethylene resin, polypropylene resin, etc.), vinyl resin (more specifically, vinyl chloride resin, polyvinyl alcohol, vinyl ether resin, N-vinyl resin, etc.), polyamide resin, and urethane resin. In addition, copolymers of these resins, that is, copolymers in which any repeating unit is introduced into the above resin (more specifically, styrene-acrylic resin, styrene-butadiene resin, etc.) can also be used as the binder resin.
[0122] The binder resin is preferably a polyester resin. The polyester resin is a polymer of one or more polyhydric alcohol monomers and one or more polycarboxylic acid monomers. Instead of the polycarboxylic acid monomer, a polycarboxylic acid derivative (more specifically, a polycarboxylic acid anhydride, a polycarboxylic acid halide, etc.) may be used.
[0123] Examples of polyhydric alcohol monomers include diol monomers, bisphenol monomers, and trihydric or higher alcohol monomers.
[0124] Diol monomers include, for example, ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, 2-butene-1,4-diol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, 1,4-benzenediol, dipropylene glycol, polyethylene glycol, polypropylene glycol, and polytetramethylene glycol.
[0125] Examples of bisphenol monomers include bisphenol A, hydrogenated bisphenol A, ethylene oxide adducts of bisphenol A, and propylene oxide adducts of bisphenol A.
[0126] Examples of trihydric or higher alcohol monomers include sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerol, diglycerol, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, and 1,3,5-trihydroxymethylbenzene.
[0127] Examples of polycarboxylic acid monomers include dicarboxylic acid monomers and tri- or higher carboxylic acid monomers.
[0128] Examples of divalent carboxylic acid monomers include maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, phthalic acid, isophthalic acid, terephthalic acid, 5-sulfoisophthalic acid, 5-sodium sulfoisophthalate, cyclohexanedicarboxylic acid, adipic acid, sebacic acid, azelaic acid, malonic acid, succinic acid, alkyl succinic acid, and alkenyl succinic acid. Examples of alkyl succinic acid include n-butyl succinic acid, isobutyl succinic acid, n-octyl succinic acid, n-dodecyl succinic acid, and isododecyl succinic acid. Examples of alkenyl succinic acid include n-butenyl succinic acid, isobutenyl succinic acid, n-octenyl succinic acid, n-dodecenyl succinic acid, and isododecenyl succinic acid.
[0129] Examples of trivalent or higher carboxylic acid monomers include 1,2,4-benzenetricarboxylic acid (trimellitic acid), 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, 1,3-dicarboxyl-2-methyl-2-methylenecarboxypropane, 1,2,4-cyclohexanetricarboxylic acid, tetra(methylenecarboxyl)methane, 1,2,7,8-octanetetracarboxylic acid, pyromellitic acid, and empol trimer acid.
[0130] The polyester resin is preferably a polymer of a bisphenol monomer, a divalent carboxylic acid monomer, and a trivalent carboxylic acid monomer, and more preferably a polymer of a bisphenol A alkylene oxide adduct, terephthalic acid, isophthalic acid, and trimellitic acid.
[0131] The polyester resin is preferably an amorphous polyester resin. For amorphous polyester resins, it is often impossible to measure a clear melting point. Therefore, a polyester resin that does not show a clear endothermic peak in an endothermic curve measured using a differential scanning calorimeter may be judged to be an amorphous polyester resin.
[0132] (Coloring agent) As the colorant, a known pigment or dye can be used in accordance with the color of the toner, and examples of the colorant include a black colorant, a yellow colorant, a magenta colorant, and a cyan colorant.
[0133] An example of the black colorant is carbon black. The black colorant may be a colorant that is toned to black using a yellow colorant, a magenta colorant, and a cyan colorant.
[0134] In the toner, the content of the colorant is preferably from 1.0 to 20.0 parts by mass, and more preferably from 3.0 to 7.0 parts by mass, relative to 100.0 parts by mass of the binder resin.
[0135] (Charge control agent) The charge control agent is used, for example, for the purpose of obtaining a toner having excellent charge stability and charge rise characteristics. The charge rise characteristics of the toner are an index of whether the toner can be charged to a predetermined charge level in a short time. Examples of the charge control agent include a positive charge control agent and a negative charge control agent. The cationic property (positive chargeability) of the toner can be strengthened by adding a positive charge control agent to the toner base particles, and the anionic property (negative chargeability) of the toner can be strengthened by adding a negative charge control agent to the toner base particles. Examples of the positive charge control agent include pyridine, nigrosine, and quaternary ammonium salts. Examples of the negative charge control agent include metal-containing azo dyes, sulfo group-containing resins, oil-soluble dyes, naphthenic acid metal salts, acetylacetone metal complexes, salicylic acid metal complexes, boron compounds, fatty acid soaps, and long-chain alkyl carboxylates. However, if sufficient chargeability is ensured in the toner, it is not necessary to add a charge control agent to the toner base particles. In the toner base particles, the content of the charge control agent is preferably from 0.1 to 5.0 parts by mass, and more preferably from 0.4 to 2.5 parts by mass, relative to 100.0 parts by mass of the binder resin.
[0136] (Release agent) The release agent is used, for example, for the purpose of obtaining a toner having excellent hot offset resistance. Examples of the release agent include aliphatic hydrocarbon waxes, oxides of aliphatic hydrocarbon waxes, plant-derived waxes, animal-derived waxes, mineral-derived waxes, ester waxes mainly composed of fatty acid esters, and waxes in which fatty acid esters are partially or completely deoxidized. Examples of the aliphatic hydrocarbon waxes include polyethylene waxes (e.g., low molecular weight polyethylene), polypropylene waxes (e.g., low molecular weight polypropylene), polyolefin copolymers, polyolefin waxes, microcrystalline waxes, paraffin waxes, and Fischer-Tropsch waxes. Examples of the oxides of aliphatic hydrocarbon waxes include oxidized polyethylene waxes and block copolymers of oxidized polyethylene waxes. Examples of the plant-derived waxes include candelilla wax, carnauba wax, Japan wax, jojoba wax, and rice wax. Examples of the animal-derived waxes include beeswax, lanolin, and spermaceti. Examples of the mineral-derived waxes include ozokerite, ceresin, and petrolatum. Examples of ester waxes mainly composed of fatty acid ester include Montan acid ester wax and castor wax. Examples of waxes in which fatty acid ester is partially or completely deoxidized include deoxidized carnauba wax. In the toner base particles, the content of the release agent is preferably 1.0 parts by mass or more and 20.0 parts by mass or less, more preferably 3.0 parts by mass or more and 10.0 parts by mass or less, relative to 100.0 parts by mass of the binder resin.
[0137] The toner particles may further contain known additives as necessary. The volume median diameter of the toner particles is preferably 4.0 μm or more and 12.0 μm or less. The volume median diameter of the toner base particles is preferably 4.0 μm or more and 12.0 μm or less, and more preferably 5.0 μm or more and 9.0 μm or less. The toner particles are preferably non-magnetic toner.
[0138] (Toner manufacturing method) An example of a toner manufacturing method will be described. The toner manufacturing method includes a toner base particle preparation step of preparing toner base particles, and an external addition step of attaching a toner external additive to the surface of the toner base particles. The toner external additive includes spacer particles.
[0139] (Toner base particle preparation process) In the toner base particle preparation step, the toner base particles are prepared by, for example, a pulverization method or an aggregation method. In the toner base particle preparation step, the toner base particles are preferably prepared by a pulverization method. That is, in the toner, the toner base particles are preferably pulverized toner base particles.
[0140] In one example of the pulverization method, first, a binder resin is mixed with other components added as necessary. The resulting mixture is then melt-kneaded using a melt-kneading device (e.g., a single-screw or twin-screw extruder). The resulting melt-kneaded product is then pulverized and classified. This produces toner base particles.
[0141] In one example of the aggregation method, first, in an aqueous medium containing fine particles of a binder resin and other components added as necessary, these fine particles are aggregated until they reach a desired particle size. This forms aggregated particles containing the binder resin and the like. The resulting aggregated particles are then heated to unify the components contained in the aggregated particles. This gives toner base particles.
[0142] (External addition process) In this step, the toner external additive is adhered to the surface of the toner base particles. For example, a method of adhering the toner external additive to the surface of the toner base particles includes a method of mixing the toner base particles and the toner external additive particles while stirring them using a mixer. EXAMPLES
[0143] The present invention will be described in more detail below using examples. However, the present invention is not limited to the scope of the examples. In the examples, the longitudinal direction of A4 size printing paper may be referred to as "vertical" and the transverse direction as "horizontal".
[0144] [Measurement of saturation magnetization and coercivity] In this example, the saturation magnetization and coercivity of the carrier core were measured using a high-sensitivity vibrating sample magnetometer ("VSM-P7" manufactured by Toei Kogyo Co., Ltd.) under the condition of an applied magnetic field of 3000 Oe.
[0145] [Surface roughness of photoconductor] The surface roughness Ra of the photoreceptor was measured by a method conforming to JIS (Japanese Industrial Standards) B0601 (geometric product specifications (GPS)-surface quality: profile curve method-terminology, definitions and surface quality parameters).
[0146] [Measurement of number average primary particle size] The number-average primary particle diameter of the particles was measured using a scanning electron microscope (field emission scanning electron microscope, "JSM-7600F" manufactured by JEOL Ltd.) In measuring the number-average primary particle diameter, the circle-equivalent diameters (Heywood diameter: diameter of a circle having the same area as the projected area of a primary particle) of 100 primary particles were measured, and the number-average value was calculated.
[0147] [Coverage measurement] The coverage of the spacer particles on the toner particles and the coverage of the carrier external additive on the carrier particles were measured by the following method. A conductive tape was fixed on a sample stage for SEM with the adhesive surface facing up. The measurement target (toner particles or carrier particles) was scattered on the adhesive surface of the conductive tape. Next, excess measurement target was removed from the adhesive surface by air blowing. Next, a medicine wrapping paper was placed on the adhesive surface, and a load was applied to the measurement target via the medicine wrapping paper, thereby fixing the measurement target to the conductive tape. Next, the medicine wrapping paper was peeled off from the adhesive surface of the conductive tape. As a result, a sample including the conductive tape and the measurement target dispersed and fixed on the adhesive surface of the conductive tape was obtained. A field emission scanning electron microscope (FE-SEM, "JSM-7600F" manufactured by JEOL Ltd.) was used to take a reflected electron image (surface image) of the surface of the measurement target of the obtained sample. The setting conditions of the FE-SEM were as follows.
[0148] (FE-SEM setting conditions for coverage measurement) Acceleration voltage of electron beam during imaging: 1kV Measurement mode: BE mode (mode that mainly detects backscattered electron signals) ·Magnification: 500x Emission current: 10μA ·Irradiation current: 450pA Shooting mode: Integration (256 times)
[0149] (Image analysis) The obtained image (surface image of the measurement object) was analyzed using image analysis software ("WinROOF" manufactured by Mitani Shoji Co., Ltd.). In the measurement, first, 10 particles were randomly selected from the measurement object. Then, the coverage A of each particle (coverage of spacer particles on toner particles or coverage of carrier external additives on carrier particles) was measured. The arithmetic average value of the measured coverage A of the 10 particles was taken as the coverage of the measurement object.
[0150] (Synthesis of amorphous polyester resin) A 5L reaction vessel equipped with a thermometer (thermocouple), a dehydration tube, a nitrogen introduction tube, and a stirring device (stirring blade) was set in an oil bath. 1575g of BPA-PO (bisphenol A propylene oxide adduct), 163g of BPA-EO (bisphenol A ethylene oxide adduct), 377g of fumaric acid, and 4g of catalyst (dibutyltin oxide) were charged into the reaction vessel. After that, a nitrogen atmosphere was created in the reaction vessel, and the temperature in the reaction vessel was raised to 220°C using an oil bath while stirring the contents.
[0151] The contents of the reaction vessel were polymerized for 8 hours under conditions of nitrogen atmosphere and temperature 220°C while distilling off by-product water. Then, after reducing the pressure inside the reaction vessel, the contents of the reaction solution were polymerized for another hour under conditions of reduced pressure atmosphere (pressure: 8 kPa) and temperature 220°C. Then, the temperature inside the reaction vessel was lowered to 210°C, and 336 g of trimellitic anhydride was added to the reaction vessel. Then, the contents of the reaction vessel were reacted under conditions of reduced pressure atmosphere (pressure: 8 kPa) and temperature 210°C. The reaction time in the reaction was adjusted so that the physical property value of the reaction product (amorphous polyester resin) was the following physical property A. Then, the reaction product was taken out of the reaction vessel and cooled to obtain an amorphous polyester resin having physical property A.
[0152] Physical properties A: Softening point (Tm) 100°C, glass transition point (Tg) 50°C, mass average molecular weight (Mw) 30,000, acid value 15 mgKOH / g, hydroxyl value 30 mgKOH / g
[0153] (Preparation of toner base particles) Using an FM mixer ("FM-10B" manufactured by Nippon Coke & Engineering Co., Ltd.), 100 parts by mass of binder resin, 4 parts by mass of colorant, 1 part by mass of charge control agent, and 5 parts by mass of release agent were mixed. As the binder resin, 100 parts by mass of the above-mentioned amorphous polyester resin (Tm: 100°C, Tg: 50°C) was used. As the colorant, copper phthalocyanine blue pigment (CI Pigment Blue 15:3) was used. As the charge control agent, quaternary ammonium salt ("BONTRON (registered trademark) P-51" manufactured by Orient Chemical Industries Co., Ltd.) was used. As the release agent, carnauba wax ("Special Carnauba Wax No. 1" manufactured by Kato Yoko Co., Ltd.) was used.
[0154] The resulting mixture was melt-kneaded using a twin-screw extruder (Ikegai Corporation, "PCM-30 type"). The resulting melt-kneaded product was pulverized using a mechanical pulverizer (Freund Turbo Corporation, "Turbo Mill"). The pulverized product was classified using a classifier (Nitetsu Mining Co., Ltd., "Elbow Jet"). This resulted in a volume median diameter (D 50 Powdered toner base particles having a particle diameter of 6.8 μm were obtained.
[0155] [Preparation of resin particles] The resin particles (RA) to (RE) were prepared by the following method.
[0156] (Resin particles (RD)) A glass reaction vessel equipped with a thermometer (thermocouple), a stirrer, a reflux condenser, and a nitrogen inlet tube was set in a water bath (set temperature: 80°C). 300.0 parts by mass of ion-exchanged water and 1.0 parts by mass of di-t-butyl peroxide were added to this reaction vessel. Next, the inside of the reaction vessel was placed under a nitrogen gas atmosphere. In the subsequent operations, the temperature of the contents of the reaction vessel was kept at 80°C, and the inside of the reaction vessel was kept under a nitrogen gas atmosphere. Next, while stirring the reaction vessel, 0.2 parts by mass of ammonium persulfate and 60.0 parts by mass of the monomer mixture were dropped into the reaction vessel over 1 hour. The monomer mixture was a mixture of 20 mol% styrene, 40 mol% butyl methacrylate, and 40 mol% divinylbenzene. Next, the contents were reacted while stirring the reaction solution. In this reaction, the reaction temperature (hereinafter sometimes referred to as "temperature T") was 100°C, the reaction time (hereinafter sometimes referred to as "time Y") was 4 hours, and the stirring speed (hereinafter sometimes referred to as "speed Z") was 756 rpm. The reaction solution (emulsion solution) after the reaction was dried to obtain crosslinked resin particles (number average primary particle diameter: 100 nm). These crosslinked resin particles were designated as resin particles (RD).
[0157] (Resin particles (RA) to (RC) and (RE)) Crosslinked resin particles (resin particles (RA) to (RC) and (RE)) having a number average primary particle diameter of 40 nm, 60 nm, 80 nm or 115 nm were prepared in the same manner as in the preparation of the above-mentioned resin particles (RD), except that the temperature X, time Y and speed Z were changed as shown in Table 1. In addition, in Table 1, "particle diameter" indicates the number average primary particle diameter.
[0158] [Table 1]
[0159] [Silica particles] Finely ground silica, carbon powder as a reducing agent, and an appropriate amount of water were put into a container and mixed to obtain a mixed raw material. The mixed raw material was then heated to about 1800°C in an incinerator to generate SiO2 gas. The generated SiO2 gas was then cooled with cooling air (flow rate X: 80 m 3 / hour) to precipitate silica fine particles. The precipitated silica fine particles were then collected using a bag filter. Aminopropylethoxysilane and silicone oil were then added to the collected silica fine particles. The silica fine particles after addition were then subjected to a heat treatment to obtain a solid matter. The solid matter obtained was then crushed using an FM mixer to obtain silica particles (Si-B) with a number-average primary particle diameter of 100 nm.
[0160] Silica particles (Si-A) were prepared in the same manner as in the preparation of silica particles B, except that the flow rate X of the cooling air was changed as shown in Table 2 below.
[0161] [Table 2]
[0162] [Toner Preparation] (Toner (T-1)) 100.00 parts by mass of the above-mentioned toner base particles, 1.50 parts by mass of base silica particles, 1.45 parts by mass of spacer particles, 0.75 parts by mass of aluminum oxide particles, and 0.5 parts by mass of strontium titanate particles were mixed for 5 minutes at 4,000 rpm using an FM mixer ("FM-10B" manufactured by Nippon Coke & Engineering Co., Ltd.). The mixture obtained was sieved using a 200 mesh (75 μm opening) sieve to obtain toner (T-1). As the base silica particles, "AEROSIL (registered trademark) REA90" manufactured by Nippon Aerosil Co., Ltd. (fumed silica with positive charging and hydrophobicity imparted by surface treatment, number average primary particle diameter: 20 nm) was used. As the spacer particles, the above-mentioned resin particles (RE) (number average primary particle diameter: 115 nm) were used. The strontium titanate particles were undoped strontium titanate particles ("SW-100" manufactured by Titan Kogyo Co., Ltd.) with adjusted particle size (number average primary particle diameter: 30 nm). The aluminum oxide particles were "AEROXIDE (registered trademark) Alu C805" manufactured by Nippon Aerosil Co., Ltd. (BET specific surface area: 75 to 105 m). 2 / g, number average primary particle size 13 nm) was used.
[0163] (Toner (T-2)~(T-8)) Toners (T-2) to (T-9) were prepared in the same manner as toner (T-1), except that the type and amount of spacer particles used were changed as shown in Table 3 below. Table 3 below also shows the coverage of the spacer particles on the toner particles. In Table 3 below, "particle size" indicates the number-average primary particle size of the spacer particles.
[0164] [Table 3]
[0165] [Preparation of carrier] Carriers (C-1) to (C-6) were prepared by the following method.
[0166] (Preparation of Carrier (C-1)) A coating liquid was obtained by mixing 361.2 g of a silicone resin solution ("KR-255" manufactured by Shin-Etsu Chemical Co., Ltd., solid concentration: 50 mass%, solid content: 180.6 g), 36.2 g of barium titanate ("BT-03" manufactured by Sakai Chemical Industry Co., Ltd., barium titanate produced by hydrothermal synthesis, number average primary particle diameter: 304 nm), 14.4 g of carbon black ("Ketjen Black EC-300J" manufactured by Lion Specialty Chemicals Co., Ltd.) and 1444.8 g of toluene using a homomixer.
[0167] Using a fluidized bed coating device (Powrex Corporation, "FD-MP-01 D type"), 5000 g of carrier cores were fluidized while spraying the coating liquid onto the carrier cores. In this way, carrier cores coated with the coating liquid were obtained. The amount of coating liquid used was an amount such that the mass of the coating layer was 1.5 parts by mass (i.e., an amount such that the solid content was 75 g) per 100.0 parts by mass of carrier cores. The coating conditions were an inlet air temperature (corresponding to the predetermined drying temperature described in the embodiment) of 75°C, an inlet air volume of 0.3 m3, and a carrier core diameter of 1.5 mm. 3 The conditions were: 1.5 rpm / min, and the rotor rotation speed was 400 rpm. Manganese ferrite cores (manufactured by DOWA IP Creation Co., Ltd., volume median diameter: 40 μm, saturation magnetization: 67 emu / g) were used as carrier cores. The carrier cores coated with the coating liquid were fired at a temperature of 200° C. for 1 hour using an electric furnace. In this way, a coating layer was formed on the surface of the carrier cores, and carrier base particles were obtained.
[0168] 100.00 parts by mass of the above-mentioned carrier base particles and 0.04 parts by mass of strontium titanate particles (external carrier additive) were mixed for 30 minutes using a rocking mixer (registered trademark) (Aichi Electric Co., Ltd. "RM-10") to adhere the strontium titanate particles to the surface of the carrier base particles. As the strontium titanate particles, non-doped strontium titanate (particle size adjusted product of "SW-100" manufactured by Titan Kogyo Co., Ltd.) with a number average primary particle diameter of 30 nm was used. Thus, carrier (C-1) was obtained.
[0169] (Preparation of Carriers (C-2) to (C-6)) Carriers (C-2) to (C-6) were prepared in the same manner as carrier (C-1), except that the amount of strontium titanate particles (external carrier additive) used and the number-average primary particle diameter were changed as shown in Table 4 below. Table 4 below also shows the coverage of the carrier particles with the external carrier additive particles. In Table 4 below, "particle diameter" indicates the number-average primary particle diameter of the strontium titanate particles (external carrier additive).
[0170] The strontium titanate particles used in the preparation of carriers (C-2) to (C-5) were all undoped strontium titanate (a particle size adjusted product of "SW-100" manufactured by Titan Kogyo Co., Ltd.). In the preparation of carrier (C-6), no external addition of strontium titanate particles (external carrier additive) was performed.
[0171] [Table 4]
[0172] <Preparation of Two-Component Developer> (Developer (D-1)) Using a shaker mixer (Turbler (registered trademark) Mixer T2F manufactured by Willy & Bachofen (WAB)), 8 parts by mass of toner (T-1) and 100 parts by mass of carrier (C-1) were mixed for 30 minutes to obtain developer (D-1) (toner ratio: 8%), which is an initial developer.
[0173] Using a shaker mixer (Turbler (registered trademark) Mixer T2F manufactured by WAB), 100 parts by mass of the above toner and 10 parts by mass of the above carrier were mixed for 30 minutes to obtain a refill developer corresponding to developer (D-1).
[0174] (Developer (D-2)~(D-15)) Except for changing the types of toner and carrier as shown in Table 5 below, developers (D-2) to (D-15) and refill developers corresponding to developers (D-2) to (D-15) were obtained in the same manner as in the preparation of developer (D-1).
[0175] [Table 5]
[0176] [Intermediate transfer belt] Intermediate transfer belts A to D shown in Table 6 were prepared.
[0177] (Intermediate transfer belt A) A polyamic acid solution (UBE Corporation's "U-Varnish", solid content 100 parts by mass) and 20 parts by mass of carbon black (Mitsubishi Chemical Corporation's "MA-100R", number average primary particle diameter 24 nm) were mixed to obtain an intermediate transfer belt forming solution. The intermediate transfer belt forming solution was subjected to centrifugal molding to form a belt shape and imidize the polyamic acid. As a result, intermediate transfer belt A (base resin: polyimide, conductive agent: carbon black) was obtained.
[0178] (Intermediate transfer belt B) 100 parts by mass of polyamide 12 (UBESTA (registered trademark) 3030U manufactured by UBE Corporation) and 15 parts by mass of carbon black (MA-100R manufactured by Mitsubishi Chemical Corporation, number average primary particle diameter 24 nm) were mixed to obtain an intermediate transfer belt forming material. The intermediate transfer belt forming material was extrusion molded into a belt shape. As a result, intermediate transfer belt B (base resin: polyamide 12, conductive agent: carbon black) was obtained.
[0179] (Intermediate transfer belt C) 100 parts by mass of PVDF ("Kynar (registered trademark) 741" manufactured by Arkema) and 60 parts by mass of titanium oxide particles ("FTL-200" manufactured by Ishihara Sangyo Kaisha, Ltd.) were mixed to obtain an intermediate transfer belt forming material. The intermediate transfer belt forming material was extrusion molded into a belt shape. In this way, intermediate transfer belt C (base resin: PVDF, conductive agent: titanium oxide particles) was obtained.
[0180] (Intermediate transfer belt D) 100 parts by mass of polyethylene terephthalate ("TR-8550" manufactured by Teijin Limited) and 20 parts by mass of polyether ester amide ("Pelestat (registered trademark) NC6321" manufactured by Sanyo Chemical Industries, Ltd.) were mixed to obtain an intermediate transfer belt forming material. The intermediate transfer belt forming material was extrusion molded into a belt shape. As a result, intermediate transfer belt D (base resin: polyethylene terephthalate, conductive agent: polyether ester amide) was obtained.
[0181] [Table 6]
[0182] [Photoreceptor] A mirror-finished aluminum raw tube (diameter: 30 mm) was subjected to wet blasting to obtain a roughened aluminum raw tube. Next, an amorphous silicon photosensitive layer (thickness: 21 μm) was formed on the surface of the roughened aluminum raw tube by vapor deposition of silane gas. In this way, photoreceptors (P-1) to (P-5) were obtained. In manufacturing the photoreceptors (P-1) to (P-5), the conditions of the wet blasting were appropriately changed to adjust the arithmetic mean roughness Ra of the surface as shown in Table 7 below.
[0183] [Table 7]
[0184] [Image forming equipment] A color multifunction printer that uses a trickle development method (TASKalfa7054ci manufactured by Kyocera Document Solutions Inc.) was prepared. This color multifunction printer mainly comprises an amorphous silicon drum as a photoconductor, a two-component development device, an intermediate transfer belt, and a cleaning blade. The printing speed of the above-mentioned color multifunction printer was a maximum of 70 sheets per minute. The development gap of the above-mentioned color multifunction printer was 0.375 mm. When printing on A4-sized printing paper, the above-mentioned color multifunction printer printed so that the width direction of the printing paper and the printing direction were aligned.
[0185] The photoconductor was removed from the above-mentioned color multifunction machine, and the above-mentioned photoconductors (P-1) to (P-5) were attached instead. The intermediate transfer belt was also removed from the above-mentioned color multifunction machine, and any one of the intermediate transfer belts A to D was attached instead. Furthermore, any one of the developers (D-1) to (D-15) was loaded into the cyan developing device of the above-mentioned color multifunction machine. Furthermore, a refill developer corresponding to each developer was loaded into the refill section of the cyan developing device of the above-mentioned color multifunction machine. As a result, image forming devices No. 1 to No. 21 were obtained, as shown in Tables 8 to 10 below.
[0186] For example, image forming apparatus No. 1 includes a photoconductor (P-4) (Ra: 100 nm) as a photoconductor. Image forming apparatus No. 1 includes an intermediate transfer belt A as an intermediate transfer belt. Image forming apparatus No. 1 includes a developer (D-1) as an initial developer. Image forming apparatus No. 1 includes a replenishment developer corresponding to developer (D-1) as a replenishment developer.
[0187] The voltage settings in the image forming apparatuses No. 1 to No. 21 were as follows. Developing bias (AC component) V ac :1300~900V Developing bias (DC component) V dc :90~280V Set surface potential of photoconductor (surface potential of non-printing area) V O :160~350V(V O -V dc= 70V) Surface potential of the printing part of the photoconductor: 10V
[0188] [Table 8]
[0189] [Table 9]
[0190] [Table 10]
[0191] <Evaluation> The image forming apparatuses No. 1 to No. 21 were evaluated for their white spot suppression performance and for the suppression of contamination of the charging roller and the photoreceptor by the following method. The evaluation results are shown in Table 11. The evaluations were performed in a low-temperature, low-humidity environment (temperature 10°C, humidity 15% RH) unless otherwise specified.
[0192] [V ac [Optimization of Regarding image forming devices No. 1 to No. 21, ac Calibrate the V ac was optimized.
[0193] [V dc Measurement of the appropriate voltage Image forming device No.1 to No.21 V dc We created multiple solid images by changing the dc The first solid image was printed on the printing paper with the V set to a predetermined value (for example, 90V). At this time, before the solid image was transferred to the printing paper, the image density of the toner image (unfixed toner image corresponding to the solid image) transferred onto the intermediate transfer belt was measured by the following method. Then, with reference to the measured image density of the toner image, V dc Increased or decreased (V dc(When the value of the toner density increases, the image density of the toner image increases.) Then, the next solid image was printed on another printing paper. This series of steps (printing the solid image on the printing paper, measuring the image density of the toner image transferred onto the intermediate transfer belt, and V dc By repeating the increase and decrease of the V dc The minimum value was calculated. The obtained minimum value was used as the V dc The measured voltage was set to the appropriate voltage. dc The appropriate voltages for are shown in Table 11 below. dc In optimizing V dc In line with the changes in V O Vary the V O -V dc =70V" was maintained.
[0194] (Measurement of image density of solid image on intermediate transfer belt) The image density of the solid image on the intermediate transfer belt was measured using a measuring device M shown in Fig. 8. In Fig. 8, a toner image S (a collection of toner T transferred onto the intermediate transfer belt B) corresponding to the solid image is formed on the intermediate transfer belt B. The measuring device M shown in Fig. 8 is a reflective optical sensor. The measuring device M uses a near-infrared light-emitting diode as the light-emitting element and a photodiode as the light-receiving element to detect the image density from the regular reflected light and the diffuse reflected light.
[0195] Specifically, the measuring device M is composed of a light-emitting unit LED, a first light-receiving unit PD1, a second light-receiving unit PD2, and a third light-receiving unit PD3 (PD: Photo Detector), and a first beam splitter BS1 and a second beam splitter BS2 (BS: Beam Splitter). The light-emitting unit LED irradiates irradiation light toward the first beam splitter BS1. The irradiation light irradiated from the light-emitting unit LED is separated by the first beam splitter BS1 into a component (s-wave light) that vibrates perpendicularly to the incident surface and a component (p-wave light) that vibrates parallel to the incident surface. The first beam splitter BS1 irradiates the first light-receiving unit PD1 disposed near the light-emitting unit LED with the s-wave light, and irradiates the intermediate transfer belt B with the p-wave light.
[0196] As shown in FIG. 8, the p-wave light irradiated to the toner T on the intermediate transfer belt B is diffusely reflected, with a portion of the light becoming an s-wave. That is, the p-wave light irradiated to the toner T is split into reflected p-wave light and reflected s-wave light. The reflected p-wave light is incident on the second light receiving element PD2 via the second beam splitter BS2 and is detected as the "amount of specularly reflected light." Meanwhile, the reflected s-wave light is incident on the third light receiving element PD3 via the second beam splitter BS2 and is detected as the "amount of diffusely reflected light." Thus, the second light receiving element PD2 functions as a specularly reflected light amount detection means, and the third light receiving element PD3 functions as a diffusely reflected light amount detection means.
[0197] In reality, it is assumed that diffuse reflection components also enter the second light receiving element PD2. Therefore, the true specular reflection output (sensor output) can be obtained by subtracting the "value obtained by multiplying the s-wave output detected by the third light receiving element PD3 by a correction coefficient" from the "p-wave output detected by the second light receiving element PD2" (see the formula below). A specified value is used as the correction coefficient. Sensor output = {specular reflection light amount (p wave) output} - {diffuse reflection light amount (s wave) output} x correction coefficient
[0198] 8, the p-wave light is irradiated onto an area (image area) on the intermediate transfer belt B where the toner T is transferred. On the other hand, when the p-wave light is irradiated onto an area (non-image area) on the intermediate transfer belt B where the toner T is not transferred, the p-wave light is almost specularly reflected and enters the second beam splitter BS2 as specularly reflected light (p-wave). The specularly reflected light that has entered the second beam splitter BS2 enters the second light receiving unit PD2.
[0199] In this measurement, a relational expression is created in advance based on the relationship between a solid image having a known image density and the sensor output. Then, the image density of the toner image S on the intermediate transfer belt B can be calculated based on the actually measured sensor output and the above-mentioned relational expression.
[0200] [Vitiligo] Regarding image forming devices No. 1 to No. 21, dc was set to the minimum value (90V). Then, using the image forming apparatuses No. 1 to No. 21, a stripe image, a solid image, and a checkered image were printed on three sheets of A4 size printing paper, respectively. When printing each image, whether or not white spots (usually about 1.5 mm wide and 0.5 mm long) occurred in the toner image transferred onto the intermediate transfer belt was detected using a measuring device M shown in FIG. 8. Specifically, the measuring device M can measure the image density in a circular measuring spot with a diameter of 3 mm at once. In detecting white spots, the measuring device M was used to measure the image density of the toner image on the intermediate transfer belt while shifting the measuring spot to be detected by 0.7 mm at a time (0.7 mm pitch). Then, when the image density measured at a specific spot was equal to or less than a certain value, or when the image density of a specific spot was equal to or more than the image density of an adjacent spot by a certain width, it was determined that white spots occurred.
[0201] The stripe image was composed of multiple parallel horizontal lines (vertical: 0.1 mm, horizontal: 6 mm) (56 lines in total, spacing between adjacent horizontal lines: 0.1 mm). The solid image was a vertical stripe-shaped solid image (horizontal: 6 cm, height: 8.6 cm). The checkered image was composed of a square printed area (solid image) with sides of 0.5 mm and a square non-printed area with sides of 0.5 mm (vertical: 6.5 mm, horizontal: 4.5 mm, total of 59 printed areas).
[0202] Next, V of image forming apparatuses No. 1 to No. 21 dc After setting the voltage 10V higher, three types of images (stripe image, solid image, and checkered image) were formed in the same manner, and the presence or absence of white spots in the toner image transferred onto the intermediate transfer belt was confirmed. dc The voltage at which white spots occur is increased by +10V, three types of images are formed, and the presence or absence of white spots is confirmed. dc The minimum value (generated voltage) was measured.
[0203] The image forming device is V dc Unless the voltage is set to a value equal to or higher than the appropriate voltage, an image having a desired image density cannot be formed. dc The higher the value, the more likely white spots are to occur. dc The appropriate voltage for and the V at which white spots occur dc The margin voltage (generated voltage - V dc If the margin voltage (the appropriate voltage for the voltage applied to the image forming apparatus) is sufficiently large, there is a low possibility that white spots will occur during actual use (the occurrence of white spots can be suppressed). On the other hand, in an image forming apparatus, if the margin voltage is small or the margin voltage is a negative value, there is a possibility that white spots will occur during actual use (the occurrence of white spots cannot be suppressed). Therefore, the magnitude of the margin voltage is used as an index of whether or not the occurrence of white spots can be suppressed. Whether or not the occurrence of white spots can be suppressed was judged according to the following criteria.
[0204] (Vitiligo criteria) A (best): Margin voltage is 31V or higher. B (particularly good): Margin voltage is 11V30V or less. C (Good): Margin voltage is between 1V and 10V. D (Fail): Margin voltage is less than 0V.
[0205] [Charging roller contamination (1K)] For each image forming device, dc was set to the appropriate voltage shown in Table 11. Next, a pattern image consisting of three horizontal stripe-shaped solid images was continuously printed on 1000 sheets of A4-sized printing paper by each image forming device (print durability test). The above-mentioned three horizontal stripe-shaped solid images were 2 mm long, 4 mm long, and 8 mm long, respectively, and the horizontal length was the upper limit of the range that can be printed on the printing paper. Next, the photoconductor of each image forming device was replaced with a new photoconductor (one of the photoconductors (P-1) to (P-5) having Ra shown in Tables 8 to 10). Next, a halftone image (hereinafter sometimes referred to as an evaluation image) was printed on one sheet of A4-sized printing paper. Next, the evaluation image was visually observed to confirm the presence or absence of image defects due to contamination of the charging roller. When the charging roller is contaminated, a portion where the image density is reduced occurs in the halftone image. The presence or absence of contamination of the charging roller was judged according to the following criteria. The result was taken as the evaluation result of "charging roller contamination (1K)".
[0206] (Standard for electrostatic roller contamination (1K)) A (particularly good): No areas of reduced image density were observed in the halftone image. B (Good): A slight decrease in image density occurred in a halftone image. C (poor): A clear area of reduced image density was observed in the halftone image.
[0207] [Charging roller contamination (10K)] For each image forming device, dc was set to the appropriate voltage shown in Table 11. Next, a pattern image consisting of the above-mentioned three horizontal band-shaped solid images was continuously printed on 1000 sheets of A4 size printing paper by each image forming device (first printing test). Next, the V acand V dc was adjusted so that a pattern image having the same image density as before the first printing durability test could be printed (adjustment step). Next, the above-mentioned pattern image was continuously printed on 1000 sheets of A4 size printing paper by each image forming device (second printing durability test). This adjustment step and second printing durability test were repeated a total of nine times. That is, a total of 10,000 pattern images were printed by combining the first printing durability test (1000 sheets printed) and the nine second printing durability tests (total of 9000 sheets printed).
[0208] Next, the photoconductor of each image forming apparatus was replaced with a new photoconductor (any of the photoconductors (P-1) to (P-5) having Ra shown in Tables 8 to 10). Next, a halftone image (hereinafter sometimes referred to as an evaluation image) was printed on a sheet of A4 size printing paper. Next, the evaluation image was visually observed to confirm the presence or absence of image defects due to contamination of the charging roller. When the charging roller is contaminated, areas with reduced image density are generated in the halftone image. The presence or absence of contamination of the charging roller was judged according to the following criteria. The results were taken as the evaluation results of "charging roller contamination (10K)".
[0209] (Standard for electrostatic roller contamination (10K)) A (particularly good): No areas of reduced image density were observed in the halftone image. B (Good): A slight decrease in image density occurred in a halftone image. C (poor): A clear area of reduced image density was observed in the halftone image.
[0210] [Photoreceptor contamination] A total of 10,000 pattern images were printed using the same method as in the evaluation of charging roller contamination (10K). Thereafter, without replacing the photoreceptor with a new one, a halftone image (hereinafter sometimes referred to as an evaluation image) was printed on a sheet of A4-sized printing paper. The evaluation image was visually observed to confirm whether or not the photoreceptor was contaminated by the toner external additive. If the photoreceptor is contaminated, image voids will occur in the halftone image. The presence or absence of contamination of the photoreceptor was judged according to the following criteria. The results were taken as the evaluation results of "photoreceptor contamination".
[0211] (Photoreceptor contamination standard) A (particularly good): No image voids occurred in halftone images. B (Good): Slight image omissions occurred in halftone images. C (poor): A clear image void occurred in a halftone image.
[0212] [comprehensive evaluation] Each image forming apparatus was comprehensively evaluated according to the following criteria. A (particularly good): The evaluation of white spots is A or B, and the evaluations of charging roller contamination (1K), charging roller contamination (10K), and photoconductor contamination are all A. B (Good): Does not fall under the overall rating of A, but there are no items rated as "bad." C (Poor): There is an item that was rated as "poor".
[0213] [Table 11]
[0214] As shown in Tables 1 to 11, image forming apparatuses Nos. 1, 4, 7 to 16, and 18 to 21 were equipped with a two-component developer containing a carrier and a toner, a photoconductor, a charging device for charging the surface of the photoconductor, a developing device for supplying toner to the surface of the photoconductor and developing it as a toner image, and an intermediate transfer belt to which the toner image is intermediately transferred. The intermediate transfer belt contained a base resin and a conductive agent. The base resin contained a thermoplastic resin or a thermosetting resin. The photoconductor had a substrate and an amorphous silicon photosensitive layer. The arithmetic mean roughness Ra of the surface of the photoconductor was 37 nm or more and 105 nm or less. The carrier contained carrier particles. The toner contained toner particles. The toner particles contained toner base particles and a toner external additive adhering to the surface of the toner base particles. The toner external additive contained spacer particles. The number average primary particle diameter of the spacer particles was larger than the arithmetic mean roughness Ra of the surface of the photoconductor. As a result, the image forming apparatuses Nos. 1, 4, 7 to 16, and 18 to 21 were able to suppress the occurrence of white spots and the contamination of the charging device and the photoconductor.
[0215] On the other hand, in image forming apparatuses No. 2, 6 and 17, the number average primary particle diameter of the spacer particles was smaller than the arithmetic mean roughness Ra of the surface of the photoconductor. Therefore, it is determined that the adhesive force between the toner particles and the photoconductor could not be sufficiently reduced by the spacer particles in image forming apparatuses No. 2, 6 and 17. As a result, image forming apparatuses No. 2, 6 and 17 could not suppress the occurrence of white spots.
[0216] In the image forming device No. 3, the Ra of the photoconductor was excessively large. Therefore, it is judged that the image forming device No. 3 was prone to a gap between the photoconductor and the cleaning blade, and the toner additives attached to the photoconductor could not be sufficiently cleaned. As a result, the image forming device No. 3 was not able to suppress the occurrence of contamination of the charging device.
[0217] In image forming device No. 4, the Ra of the photoconductor was too small. Therefore, it is determined that the cleaning blade of image forming device No. 4 was worn down with use, and the toner additives attached to the photoconductor could not be sufficiently cleaned. As a result, image forming device No. 4 was unable to suppress the occurrence of contamination of the charging device. [Industrial Applicability]
[0218] The image forming apparatus of the present invention can be used to form images in, for example, a copier, a printer, or a multifunction machine. [Explanation of symbols]
[0219] 1. Carrier particles 2. Carrier mother particles 2a Career Core 2b Coating layer 3. Carrier additives 4 Toner particles 5 Toner base particles 6 Toner additives 6a Spacer particles 6b Silica particles 11 Developing device 12 Photoreceptor 13 Intermediate transfer belt 21 Charging device 100 Image forming device
Claims
1. a two-component developer including a carrier and a toner; A photoconductor; a charging device for charging the surface of the photoreceptor; a developing device that supplies the toner to the surface of the photoconductor and develops the toner image; an intermediate transfer belt onto which the toner image is intermediately transferred; the intermediate transfer belt contains a base resin and a conductive agent; The base resin comprises a thermoplastic resin or a thermosetting resin, The photoreceptor has a substrate and an amorphous silicon photosensitive layer, The arithmetic mean roughness Ra of the surface of the photoreceptor is 37 nm or more and 105 nm or less, The carrier comprises carrier particles, The toner comprises toner particles, the toner particles include toner base particles and a toner external additive attached to a surface of the toner base particles, the toner external additive contains spacer particles, the number average primary particle diameter of the spacer particles is greater than the arithmetic mean roughness Ra of the surface of the photoreceptor.
2. 2. The image forming apparatus according to claim 1, wherein a coverage of the spacer particles on the toner particles is 7 area % or more and 45 area % or less.
3. The image forming apparatus according to claim 1 , wherein the spacer particles include resin particles.
4. The image forming apparatus according to claim 1 , wherein the spacer particles include silica particles.
5. 3. The image forming apparatus according to claim 1, wherein the number average primary particle diameter of the spacer particles is 45 nm or more and 140 nm or less.
6. The carrier particles include carrier base particles and carrier external additives attached to the surfaces of the carrier base particles, 3. The image forming apparatus according to claim 1, wherein the number average primary particle diameter of the external carrier additive is smaller than an arithmetic mean roughness Ra of the surface of the photoconductor.
7. 7. The image forming apparatus according to claim 6, wherein a coverage of the carrier particles with the external carrier additive is 5.0 area % or more and 35.0 area % or less.
8. The image forming apparatus according to claim 6 , wherein the external carrier additive contains strontium titanate particles.
9. The image forming apparatus according to claim 6 , wherein the number average primary particle diameter of the external carrier additive is 15 nm or more and 85 nm or less.
10. The substrate has a roughened surface, 3. The image forming apparatus according to claim 1, wherein the roughened surface is subjected to a blasting treatment.
Citation Information
Patent Citations
Developing device, process cartridge, and image forming apparatus
JP2016071305A